À propos d’une œuvre promise à la disparition de Claire Pentecost - Claire Valageas; Chloé Barle (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This conservation-restoration project for Proposal for a New American Agriculture by Claire Pentecost, conducted in 2021-2022, fostered interdisciplinary dialogue between Claire Valageas (49 Nord 6 Est - Frac Lorraine), Chloé Barle (a student in textile arts conservation-restoration), and the artist herself. By combining their perspectives, this collaboration allowed for a conservation approach addressing the work’s presentation, reception, and the preservation of its material and conceptual integrity.